Misdiagnosed Aicardi Goutières Syndrome Patient: A Case Report - Mohammad Moein Vakilzadeh; Najmeh Ahangari; Ehsan Ghayoor Karimiani; Mehran Beiraghi Toosi (Reviews in Clinical Medicine, 2021)
Aicardi Goutiere’s syndrome is an autosomal recessive neurodegenerative disorder. Its clinical signs usually mimic TORCH-like clinical signs; which makes the differential diagnosis difficult. Here, we report a case with one homozygous pathogenic mutation c.529G>A p.Ala177Thr on RNASEH2B gene (NM_024570) that relates to Aicardi-Goutieres syndrome type 2  that had been misdiagnosed in about 5 years.